PSYCHOLOGI IMPACT PF CHILDREN ON CONFLICT WITHSTEPMOTHERS - sartika, refa; fitriani, wahidah; yeni, putri (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
Abstrack:The psychological impact of a child experiencing conflict with his mother, he continued, is in the form of things such as making the child stressed, anxious and like he has lost direction because no one can understand him. This conflict also makes him not believe in himself. And this article aims so that parents out there can understand their children and not just obey their own egos. And in this article we will also discuss what conflicts with continuous mothers are, how they impact children's psychology, the factors that cause conflict, and what strategies to handle these problems. And an invitation to readers to understand the feelings of children who are in conflict with their mothers